2006
DOI: 10.1182/blood-2005-12-040972
|View full text |Cite
|
Sign up to set email alerts
|

Bcr-Abl signaling through the PI-3/S6 kinase pathway inhibits nuclear translocation of the transcription factor Bach2, which represses the antiapoptotic factor heme oxygenase-1

Abstract: The malignant phenotype of chronic myeloid leukemia (CML) is due to the abnormal tyrosine kinase activity of the Bcr-Abl oncoprotein. We have previously reported that expression of the Bach2 transcription factor, which induces apoptosis in response to oxidative stress, is greatly reduced in CML cells. Because these cells are resistant to apoptosis, we tested whether Bach2 could also be regulated through posttranslational mechanisms that promote inhibition of the apoptotic response to mutagenic stimuli in CML. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
48
0

Year Published

2008
2008
2017
2017

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 51 publications
(53 citation statements)
references
References 64 publications
(81 reference statements)
5
48
0
Order By: Relevance
“…Therefore, phosphorylation of these residues may induce a conformational change of the disordered region, thereby regulating its function such as protein interaction. Human BACH2 is phosphorylated at Ser-521, which inhibits BACH2 nuclear accumulation in NIH3T3 cells (27). This site corresponds to Ser-520 of mouse Bach2, which was phosphorylated in our mass spectrometry analysis.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Therefore, phosphorylation of these residues may induce a conformational change of the disordered region, thereby regulating its function such as protein interaction. Human BACH2 is phosphorylated at Ser-521, which inhibits BACH2 nuclear accumulation in NIH3T3 cells (27). This site corresponds to Ser-520 of mouse Bach2, which was phosphorylated in our mass spectrometry analysis.…”
Section: Discussionmentioning
confidence: 99%
“…Although Bach2 has been reported as a phosphoprotein (27), this study is the first systematic analysis of its phosphorylation using normal primary B cells. By using the presence of a slower moving band of Bach2 upon immunoblotting as a proxy of its phosphorylation, we found that Bach2 phosphorylation was reduced by treating cells with the inhibitors of PI3K, Akt, or mTOR but not by those of MEK or p38 MAPK (Figs.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Regarding human Bach2, the phosphorylation of serine 521 is required for the cytoplasmic accumulation of Bach2. This modification is dependent on the PI-3K/S6 kinase pathway, thus raising the possibility that Bach2 is regulated via phosphorylation in response to extracellular cytokines and growth factors (Yoshida et al 2007). In addition to this site, we recently found that additional multiple sites of Bach2 are modified by phosphorylation in response to the PI-3K pathway (Ando R., Shima H., Sato Y., Muto A. and Igarashi K., unpublished observation).…”
Section: Regulation Of Bach By Redox and Phosphorylationmentioning
confidence: 99%